“Old-New” Directions in Political Communication: Taking Michael Parenti's Media Criticism as a Guide - Bergman, Tabe (Frontiers in Communication, 2019)
In this essay I outline where I think the study of political communication should go – or rather, return back to. First I discuss existing limitations and weaknesses of the current subfield of political communication, after which I highlight the work of political scientist Michael Parenti as an example of scholarship that I would like to see more of, especially in Frontiers in Political Communication. In the Conclusion I summarize my main points and specify what I think should be priorities for scholars of political communication, as the world moves forward through these precarious times for democracy, justice, and even species survival.